Donor-derived ALECT2 Amyloidosis in a Transplant Allograft: A Rare Scenario - Kanupriya Agrawal; Mahendra Meena; Arjun Agarwal; Rakesh Gupta; Dhananjai Agarwal (Indian Journal of Transplantation, 2025)
Leukocyte chemotactic factor 2 amyloidosis is a recently recognized entity that often affects the kidneys. Little information is available regarding kidney transplant outcomes in patients with LECT2 amyloidosis or who received kidney allografts containing LECT2 amyloid. We present the clinical course and outcome of a patient who received a kidney with donor-derived LECT2 amyloidosis. The patient was a 30-year-old male who received live-related renal allograft from a 57-year-old female. Allograft biopsy was done on day 7 posttransplant due to slow graft function with creatinine = 1.9 mg/dl. Biopsy was consistent with the findings of thrombotic microangiopathy (TMA) with donor-derived interstitial amyloid deposition staining positive for ALECT2. TMA was probably de novo due to dose-dependent tacrolimus toxicity. Tacrolimus level was around 14 ng/ml on 3 mg BD as given according to body weight 0.1 mg/kg. After reducing the dose, creatinine level reduced to 1.1 mg/dl. The donor was thoroughly evaluated for cause and any systemic manifestation of amyloidosis; she also did not develop any systemic manifestations yet. After 1-year regular follow-up, the recipient is maintaining well with creatinine around 1 mg/dl. The indolent posttransplantation course suggests that donated kidneys with ALECT2 amyloidosis may be suitable for transplantation, but the deposits persist for many years.